1997
DOI: 10.1007/bf02439554
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and bone scintigraphy in children and adolescents with osteomalacia

Abstract: In order to demonstrate the role of bone mineral density (BMD) measurement and bone scans in the management of patients with osteomalacia, radioisotope bone scintigraphy using technetium-99m methylene diphosphonate (MDP) and BMD measurements of the lumbar spine and femur by means of dual X-ray absorptiometry (DXA) were performed at the time of diagnosis and 6 months after therapy in 26 Saudi patients (17 females and nine males). Their mean age was 13.5 years (range, 5-16). BMD measurements were compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 8 publications
1
35
0
Order By: Relevance
“…A pseudofracture may be transferred to a true fracture, as a result of stress on the weak bone zone. No patient in our study got a true fracture as we agree with other authors [29]- [32], who reported that Pseudofractures often heal with calcium and vitamin D supplements if the diagnosis is made early. But, we add to them the high index of suspicion and adherence of the patients to the treatment protocol and instructions to avoid the potentially serious complications including true fractures.…”
Section: Discussionsupporting
confidence: 92%
“…A pseudofracture may be transferred to a true fracture, as a result of stress on the weak bone zone. No patient in our study got a true fracture as we agree with other authors [29]- [32], who reported that Pseudofractures often heal with calcium and vitamin D supplements if the diagnosis is made early. But, we add to them the high index of suspicion and adherence of the patients to the treatment protocol and instructions to avoid the potentially serious complications including true fractures.…”
Section: Discussionsupporting
confidence: 92%
“…No differences in mineralisation were identified. Conversely, a report of 26 children and adolescents with osteomalacia and/or rickets in Saudi Arabia suggested that aBMD z-scores at the LS and FN femur were reduced, and that these improved following calcium and vitamin D therapy [52]. It is unclear though whether these differences were statistically significant.…”
Section: Vitamin D and Bone Mineralisation Bone Mineral Density In Vimentioning
confidence: 99%
“…El Desouki et al performed total body scintigraphy in 26 children and adolescents with rickets or osteomalacia. They reported that "multiple stress fractures" were present in 8 (31%) of the participants and healing was evident 6 months after vitamin D and calcium therapy [52]. However, these "pseudofractures" were not confirmed radiologically, and may have represented Looser zones rather than true fractures.…”
Section: Fracture In Children With Vitamin D Deficiency Ricketsmentioning
confidence: 99%
“…Despite the generally null findings of randomized controlled trials of vitamin D supplementation on bone end‐points, it is quite clear that very low levels of vitamin D result in osteomalacia, which is associated with reduced bone density as well as with musculoskeletal symptoms. Treatment of osteomalacia results in substantial increases in bone density . It has not been established what the threshold is, in terms of baseline serum 25‐hydroxyvitamin D, for any beneficial effects of vitamin D supplementation on bone density to occur.…”
Section: Introductionmentioning
confidence: 99%